Contestation and the Roles of Islam in The Public Sphere: A Sociological Analysis of Religious Secularization in Indonesia and the West - Mohammad Takdir (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
This study aims to explain the contestation of Islam in the public sphere. As the majority religion, Islam always presents a debate about the position of Islam in the public sphere which is often misused for political and power interests. This study uses a comparative study between secularization practices in Indonesia and the West. The theory used in this study is Jurgen Habermas’ view of the public sphere, which is an open means of making every citizen a communicative society. This study shows that the contestation of Islam in the public sphere is very hard by following the ideology of a country in placing symbols and Islamic identities in the public sphere. In Indonesian context, restrictions on religious expression cannot be restricted, let alone to be prohibited by the state as the holder of power.